2006
DOI: 10.1007/s00535-006-1894-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression between flat adenoma and normal mucosa in the colon in a microarray analysis

Abstract: This is the first report characterizing the genes differentially expressed in flat adenomas using a microarray analysis. Considerable differences in the gene expression profiles of flat adenomas also exist between the right and left colon. These data should lead to new insights into the pathogenesis of flat adenomas in the colon as well as to new therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 34 publications
4
35
0
Order By: Relevance
“…We found that Duox2 was highly expressed in colorectal cancers. That finding is supported by the observation that pre-malignant adenomatous lesions of the large intestine demonstrate a 10-fold increase in DUOX2 expression when compared with adjacent non-malignant tissues from the same patients (42). Finally, we have recently conducted an immunohistochemical evaluation of Duox2 expression using tumor tissue microarrays; in that investigation, we found increased Duox2 levels, compared with non-malignant control tissues, in adenocarcinomas of the stomach, colon, and pancreas.…”
Section: Discussionsupporting
confidence: 53%
“…We found that Duox2 was highly expressed in colorectal cancers. That finding is supported by the observation that pre-malignant adenomatous lesions of the large intestine demonstrate a 10-fold increase in DUOX2 expression when compared with adjacent non-malignant tissues from the same patients (42). Finally, we have recently conducted an immunohistochemical evaluation of Duox2 expression using tumor tissue microarrays; in that investigation, we found increased Duox2 levels, compared with non-malignant control tissues, in adenocarcinomas of the stomach, colon, and pancreas.…”
Section: Discussionsupporting
confidence: 53%
“…In the case of colon cancer, this neoplasm results from a progressive series of steps whereby epithelial dysplasia evolves into a flat adenoma, carcinoma in situ, and finally, adenocarcinoma. Of note is that ODAM expression is increased ~6-fold in the earlier stage of disease, i.e., flat adenoma, as compared with the normal mucosa (36). Notably, epidermal growth factors such as ampiregulin, epigen, and epiregulin, which are found in a variety of human cancers, including those of breast and gastrointestinal origin, map to the identical chromosomal band (4q13.3) and are present in a cisoriented cluster on the same DNA strand as ODAM and FDC-SP (37).…”
Section: Discussionmentioning
confidence: 95%
“…Despite the high incidence of colorectal adenomas, surprisingly few microarray studies have been performed comparing normal mucosa and adenomas (Lin et al, 2002;Kita et al, 2006;Sabates-Bellver et al, 2007;Galamb et al, 2008). Performing analysis on premalignant phenotypes is of special interest as these lesions represent a relatively homogeneous condition, providing information about the initial changes during colorectal carcinogenesis and about putative targets for chemoprevention.…”
Section: Introductionmentioning
confidence: 99%